Context into text into context: marketing practice into theory; marketing theory into practice. Issue 7 (5th October 2015) - Smith, Terry; Williams, Tom; Lowe, Sid; Rod, Michel; Hwang, Ki-Soon
Abstract : Purpose: – The purpose of this paper is to explore the dynamics of marketing practice and theory in arguing that much of the dislocation between strategy and practice is due to the inheritance and internalisation of often impractical but persistently dominant, tacit Cartesian assumptions. Design/methodology/approach: – This paper uses case methodology to examine the marketing theory into practice/marketing practice into theory conundrum and explores: their separation (marketing theory and marketing practice); their flows (context to text to context: theory into practice/practice into theory); their symbiosis (the praxis of marketing); and the dynamic and static ( in situ / in aspic ) nature of their duality. This work is an exploratory empirical study undertaken in what is a very under-researched area. Findings: – In this paper, marketing theory and marketing practice are recognised as occupying different epistemes. The lifeworld of marketing theorising appears as characterised by a relatively homogenous and mostly cognitive world dominated by rationality and empirical rigour. By contrast, the embodied practitioner inhabits a more highly segmented, fragmented, heterogeneous and frequently improvised landscape. Practical implications: – The authors propose that the all-consuming clamour for reliance and relevance of theory to practice dictates that the form, function and philosophy of marketing must be co-created in the practical pragmatism of praxis. Praxis is practice informed by theory and theory informed by practice, a cyclical process of experiential, contextual learning. Originality/value: – The paper appears to be the first to bring together Cartesian thought and the practice-theory divide in B2B marketing theory.